2019
DOI: 10.3892/ol.2019.9964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dezocine and sufentanyl for postoperative analgesia on activity of NK, CD4+ and CD8+ cells in patients with breast cancer

Abstract: The effects of dezocine and sufentanyl on the activity of natural killer (NK), CD4 + and CD8 + cells in patients with breast cancer undergoing postoperative analgesia after radical mastectomy were compared. The clinical data of 76 female patients undergoing radical mastectomy in the Fudan University Shanghai Cancer Center from January 2015 to October 2017 were analyzed retrospectively. Forty-two patients treated with dezocine were group D and 34 patients with sufen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Emerging evidence has reported that dezocine could regulate immune function of cancer patients after surgery [19]. In this study, we investigated the anti-tumor activity of dezocine on ovarian cancer cells for the first time and demonstrated that dezocine could inhibited the viability of ES-2 and SKOV3 cells in a dose-independent manner.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Emerging evidence has reported that dezocine could regulate immune function of cancer patients after surgery [19]. In this study, we investigated the anti-tumor activity of dezocine on ovarian cancer cells for the first time and demonstrated that dezocine could inhibited the viability of ES-2 and SKOV3 cells in a dose-independent manner.…”
Section: Discussionmentioning
confidence: 92%
“…Feng C et al previously reported that dezocine could regulate the secretion of IL-12 and IL-10 in dendritic cells, and enhance the activity of T cells during the maturation of dendritic cells, affecting immune function [18]. Wang F et al found that dezocine reduces the inhibitory effect of NK cells and CD4 + activity and the activity of CD8 + cells in breast cancer patients undergoing radical mastectomy, which is beneficial to the recovery of immune function [19]. These studies suggest that dezocine plays an important role in immune function.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has reported that dezocine could regulate the immune function of cancer patients after surgery [19]. In this study, we investigated the anti-tumor activity of dezocine on ovarian cancer cells for the rst time and demonstrated that dezocine could inhibit the viability of ES-2 and SKOV3 cells in a dose-independent manner.…”
Section: Discussionmentioning
confidence: 93%
“…Feng C et al previously report that dezocine could regulate the secretion of IL-12 and IL-10 in dendritic cells and enhance the activity of T cells during the maturation of dendritic cells, affecting immune function [18]. Wang F et al show that dezocine reduces the inhibitory effect of NK cells and CD4 + activity and the activity of CD8 + cells in breast cancer patients undergoing radical mastectomy, which is bene cial to the recovery of immune function [19]. These studies suggest that dezocine plays an important role in immune function.…”
Section: Introductionmentioning
confidence: 98%
“…One study showed that dezocine was more beneficial to the recovery of the early postoperative immune function of patients with breast cancer undergoing postoperative analgesia after radical mastectomy. 10 A study by Song et al 17 revealed that dezocine can inhibit tumour metastasis by elevating CD8+ T cell proliferation and cytotoxicity. Zhu et al 32 revealed that dezocine and ropivacaine infiltration anaesthesia can significantly inhibit the secretion of pain factors in patients undergoing open hepatectomy, as well as reduce the stress response after surgery, reduce immune function fluctuations and help promote postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%